Employee Performance Model Through Job Satisfaction: Distributive Justice and Procedural Justice at the Padang Sidempuan City Health Office - Letnan Dalimunthe; Nandan Limakrisna; Lusiana Lusiana (Universitas Pendidikan Ganesha, 2023)
Organizations must concentrate on their human resources to perform their functions optimally in order to create a more advanced organization, especially in light of impending environmental changes. This research aims to analyze the relationship between distributive justice and procedural justice, as well as their impact on job satisfaction, among health office workers. This study is use quantitative method. Total of 285 workers involving in this study as subjects. This study was used surveyed for the research. In analyzing data SEM PLS was used to analyze the collected data. The result of this study found employee performance at Health Office is influenced by distributive justice, procedural justice, and job satisfaction. The impact of distributive justice on employee performance is mediated by job satisfaction; the impact of procedural justice on employee performance as mediated by job satisfaction. In order to promote procedural justice management have to improves on-time work completion, fair implementation of leadership decisions, provision of a pleasant working environment, encouragement of positive attitudes among workers, and the dissemination of accurate and up-to-date information.